Is the QBS-ar index a good tool to detect the soil quality in Mediterranean areas? A cork tree Quercus suber L. (Fagaceae) wood as a case of study - Galli, L.; Capurro, M.; Menta, C.; Rellini, I. (Italian Journal of Zoology, 2014)
Abstract Cork oak (Quercus suber L., 1753) is a Mediterranean evergreen tree species with a thick and characteristic bark covering the trunk and branches. Despite the fact that cork oak is distributed over about 1.7 million hectares in the western Mediterranean Basin, information about soil biota in this particular habitat at present is scanty. This study was carried out in a cork tree wood in Bergeggi (Liguria, NW Italy), characterized by a Pluvioseasonal Oceanic Mediterranean bioclimate. The profile, texture, pH, total carbonate content, total organic carbon (C) and nitrogen (N) contents, soluble phosphorus (P) and cation exchange capacity were measured in order to characterize the soil. Soil biological quality was evaluated by studying microarthropod communities. Each month, from February 2007 to January 2008, 10 soil samples measuring 10 ? 10 ? 10 cm were collected from the wood being studied and arthropods were extracted using Berlese-Tullgren funnels. The biological quality of soil based on arthropods (QBS-ar) index, taxa abundance, Shannon diversity index (H?) and Pielou?s evenness index (J) were applied to assess soil biological quality in the cork oak being studied. A total of 29 taxonomic groups were identified. Some important groups, such as Pseudoscorpionida, Palpigradi, Miriapoda and Protura were detected every month, but only a few groups showed a clear abundance distribution trend throughout the year and globally it was impossible to define general trends. The results suggested that the condition of the soil was good, as generally observed in natural environments not subjected to significant impacts. It was also possible to demonstrate that the Mediterranean climate causes strong seasonal fluctuations in soil biota, resulting in corresponding differences in the QBS-ar index values. Therefore, the QBS-ar index could be considered to be a valid candidate for the biomonitoring of soil biodiversity in natural and anthropic soils, but in Mediterranean climates comparisons of different areas must be performed analyzing samples collected during the same period.
From Duplicate 2 (Is the QBS-ar index a good tool to detect the soil quality in Mediterranean areas? A cork tree Quercus suber L. (Fagaceae) wood as a case of study - Galli, L; Capurro, M; Menta, C; Rellini, I)From Duplicate 2 (Is the QBS-ar index a good tool to detect the soil quality in Mediterranean areas? A cork tree Quercus suber L. (Fagaceae) wood as a case of study - Galli, L; Capurro, M; Menta, C; Rellini, I)The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Biological index; Cork Oak Forest; microarthropods; QBS-ar; soil quality